2017
DOI: 10.1016/j.jbusres.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

From conformity to reactance: Contingent role of network centrality in consumer-to-consumer influence

Abstract: International audienceCentral consumers in a group often are influential, because their social prominence commands conformity from other members. Yet, there can be another contradictory effect of centrality, such that other members regard it as a threat to their attitudinal freedom and express reactance instead of conformity. Whether a group member conforms or reacts to the evaluation of a more central member might depend on the strength of their relationship, which determines the social cost of disagreeing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 76 publications
2
20
0
1
Order By: Relevance
“…Similarly, it was found that the effect of provider satisfaction on positive WOM is more positive in the non-employer group. These two findings support the notion that less reactance influences satisfaction and positive WOM to a greater extent (Chatterjee et al, 2017).…”
Section: Theoretical Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, it was found that the effect of provider satisfaction on positive WOM is more positive in the non-employer group. These two findings support the notion that less reactance influences satisfaction and positive WOM to a greater extent (Chatterjee et al, 2017).…”
Section: Theoretical Discussionsupporting
confidence: 84%
“…Annoyance (Kelly et al, 2017), perceptions of unfairness (White et al, 2012) and decreased service evaluations (Reinders et al, 2015) have been shown to occur when free choice or alternates are limited. Thus, leading to less positive evaluations of current consumption options (Brehm and Brehm, 1981;Chatterjee et al, 2017), and thus, lowering satisfaction (Chatterjee et al, 2017).…”
Section: Psychological Reactance Theorymentioning
confidence: 99%
“…Consequently, they acquire more knowledge and potentially have a greater capacity of monitoring their external environment and verifying valuable resources or technologies (Ahuja, 2000;Mazzola et al, 2015). As such, knowledge network centrality could help firms to be more familiar to the knowledge-processing mechanisms of the external partners, thus ultimately reducing the uncertainty and enhancing their search for high-quality partners in technology innovation (Chatterjee et al, 2017). Thus, as compared to other firms, the positive returns of external search breadth in collaboration networks will likely to be enlarged if the focal firm is located in the central position in knowledge networks.…”
Section: 31mentioning
confidence: 99%
“…For instance, Hwan et al (2010) find that having greater centrality leads consumers to see themselves as more important than other consumers within a social network. A consumer’s gift-giver centrality is likely to influence the entire network; the more central a consumer is in a network, the greater impact the consumer has on the behaviors of other consumers in the network (Chatterjee et al , 2017; Richards et al , 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%